Birds and bovids: new parietal engravings at the Romanelli Cave, Apulia. (December 2021) - Sigari, Dario; Mazzini, Ilaria; Conti, Jacopo; Forti, Luca; Lembo, Giuseppe; Mecozzi, Beniamino; Muttillo, Brunella; Sardella, Raffaele
Abstract : ABSTRACT: The Romanelli Cave in south-east Italy is an important reference point for the so-called 'Mediterranean province' of European Upper Palaeolithic art. Yet, the site has only recently been subject to a systematic investigation of its parietal and portable art. Starting in 2016, a project has recorded the cave's interior, discovering new parietal art. Here, the authors report on a selection of panels, featuring animal figures, geometric motifs and other marks, identifying the use of different types of tools and techniques, along with several activity phases. These panels are discussed with reference to radiocarbon dating of nearby deposits, posing questions about chronology, technology and wider connections between Upper Palaeolithic cave sites across western Eurasia.